Analisis Konjoin pada Pengukuran Preferensi Mahasiswa FMIPA UNP dalam Memilih Smartphone - Sismita Sari; Suherman Suherman; Minora Longgom Nasution (UNIVERSITAS NEGERI PADANG, 2021)
Abstract – Currently, the smartphone comes with a variety of attributes, such as RAM, camera, battery, display and prices vary. The variety of smartphones make consumers can choose the desired product. Based on these problems, then the problem formulation in this research is what most influential attributes against the preferences of FMIPA UNP’s students in choosing a smartphone. The population of this research are all students of FMIPA UNP with sample as much as 190 respondents. In this research, the data used is primary data. Data analysis techniques used are Conjoint Analysis. From the results of data analysis, retrieved the importance attribute for each attribute RAM, camera, battery, display, and consecutive registration 37,402%, 12,342%, 9,623%, 7,772%, and 32,862%. Based on the importance of these attributes retrieved conclusion that attribute that most influences the referrers students of FMIPA UNP in choosing a smartphone is the attribute of the RAM. Keywords – smartphone, preferences, attributes, conjoint analysis